RESEARCH IN ONLINE SPACE: THE USE OF SOCIAL MEDIA FOR RESEARCH SETTING - Nurdin Nurdin (Jurnal Sistem Informasi, 2017)
Web 2.0 technology has supported the arrival of various social and collaborative applications. Those applications, which is known as social media, provide an opportunity for  users to express their opinions and share their knowledge and thoughts with others in online space.  This provides opportunities for reseachers to extend their research setting and generate data within a broader environement. As a result, researchers have increasingly turned to social media sites  to practice their research  to expand the scope and improve the analytic power of their studies. Yet there is still relatively little direction on and much confusion about how to gather data using qualitative and quantitative approaches on social media sites. Through an exstensive literature review from Information Technology and Information System journals, this studi  proposes new data gathering strategies within a broader environment of social media sites.   This study contributes to understanding of using social media for new  research settings. The limitation and future research of this study is addressed.